The Relationship between BMI and Menstrual Cycle Disorders in Adolescent Girls in the Working Area of the Posi Posi Community Health Centre - Lisawan Yoseph Lobo; Tut Rayani Aksohini Wijayanti (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Menstrual cycle disorders are reproductive health problems commonly experienced by adolescent girls and can reflect endocrine imbalances and nutritional status. Body mass index (BMI) is known to play a role in regulating reproductive function, but empirical evidence based on primary health care services, especially in non-metropolitan areas, remains limited. This study aims to analyse the relationship between body mass index and menstrual cycle disorders in adolescent girls in the working area of Posi Posi Community Health Centre. This study used a quantitative observational cross-sectional analytical design. The subjects consisted of 78 adolescent girls aged 10–19 years who had experienced menstruation and met inclusion criteria. Data were collected through structured questionnaires to assess menstrual cycles and anthropometric measurements to determine BMI. Data analysis was conducted using univariate and bivariate methods with the chi-square test at p < 0.05. The results showed that most respondents had normal BMI, although abnormal BMI proportions remained notable. Menstrual disorders were more frequent among underweight, overweight, and obese adolescents compared to those with normal BMI. Statistical analysis indicated a significant relationship between BMI and menstrual disorders. In conclusion, BMI is significantly associated with menstrual cycle disorders in adolescent girls. These findings emphasise the importance of monitoring nutritional status as part of adolescent reproductive health services through promotive and preventive approaches. Furthermore, community health centres should strengthen education, early detection, and counselling programs to prevent complications and improve adolescents’ overall health outcomes and quality of life in the future generations sustainably for long term wellbeing overall.